Complexation of europium(iii) with exopolysaccharides from a marine bacterium envisaged as luminescent probe in a theranostic approach. Issue 46 (16th November 2021) - Huclier-Markai, Sandrine; Alliot, Cyrille; Mazza, Mattia; Reiller, Pascal E.
Abstract : Exopolysaccharide (EPS) derivatives, produced by Alteromonas infernus bacterium, showed anti-metastatic properties in osteosarcoma (bone tumor). Abstract : Exopolysaccharide (EPS) derivatives, produced by Alteromonas infernus bacterium, showed anti-metastatic properties in osteosarcoma (bone tumor). These EPSs could be employed as new drug delivery systems for therapeutic uses. They may represent a new class of ligands to be combined in a theranostic approach with fluorescent metals, such as Eu(iii ), to serve as imaging probe. The goal of this work was to investigate the feasibility of such coupling by time-resolved laser-induced fluorescence spectroscopy (TRLFS). Since these EPSs are polyelectrolytes their conformation could affect the complexation properties. Thus, viscosimetric measurements were performed as a function of their concentration as well as the background electrolyte concentration. Polysaccharides conformation exhibited a lower hydrodynamic volume for the highest ionic strengths. The resulting random-coiled conformation could affect the complexation with metal for high concentration but no change was evidenced when increasing europium concentration. Two sites of complexation of Eu(iii ) were evidenced by TRLFS in heparin, whereas only one site was evidenced in two modified EPSs produced from Alteromonas infernus .